A Case of Congenitally Corrected Transposition of Great Arteries (CCTGA) (Community Based Medical Journal, 2015)
Recent years, much scientific attention has been given to congenital heart diseases (CHD) and probable complications. Congenitally corrected transposition of the great arteries (CCTGA) is a rare, complex form of congenital heart defects. CCTGA is characterized by atrioventricular (AV) and ventriculoarterial (VA) discordance and hence by a physiologically normal direction of blood flow sometimes called "double discordance". The development of complete AV block and global ventricular dysfunction has been identified as the cause of cardiac death. This paper presents a case of CCTGA with rhythm disorders and exertional dyspnea.CBMJ 2015 January: Vol. 04 No. 01 P: 37-40